European Academy of Paediatrics statement on the clinical management of children and adolescents with gender dysphoria - Brierley, Joe; Larcher, Vic; Hadjipanayis, Adamos A.; Grossman, Zachi (Frontiers in Pediatrics, 2024)
Gender issues have become a polarised and political subject in modern paediatrics and indeed, in broader society. These include the management of infants with disorders of sex development and transgender sports participation, but especially recently regarding the management of gender dysphoria. The European Academy of Paediatrics (EAP) acknowledges that there are deeply held beliefs about this issue based on conscience and social norms. Several European countries, led by the UK, have recently reviewed the management of gender dysphoria in children and young people.Recognising the need for far more research into treatments such as pubertal suppression and cross-sex hormones in children and young people, we review the current ethical and legal dilemmas facing children with gender dysphoria, their families and the clinical teams caring for them. We suggest an approach that maintains the child's right to an open future whilst acknowledging that the individual child is the crucial person affected by decisions made and must receive appropriate support in decision-making and care for any associated mental health or psychological issues.Noting that national approaches to this vary and are in flux, the EAP advocates a child-centred individual rights-based analytical approach.